An experimental assessment of the nall lexical gap - Zhou, Ruizhe; Spector, Benjamin; Maldonado, Mora (Proceedings of the Amsterdam Colloquium, 2024)
Across the world’s languages, the quantificational concept not all (nall) is never lexicalized. This also holds for temporal (not always), modal (not must) and locative (not everywhere) domains. Existing accounts for these lexical gaps fall into two broad categories. According to Cognitive Markedness accounts, nall is not lexicalized because it expresses a cognitively unnatural concept. According to Communicative Efficiency accounts, nall is not intrinsically marked, but is not very useful for efficient communication. Across two artificial language learning experiments, we found no cognitive bias against nall, suggesting that its absence from the lexicon cannot be attributed to cognitive markedness.